Brazil - Country Note on Climate Change Aspects in Agriculture - World Bank (Washington, DC, 2012)
This country note briefly summarizes information relevant to both climate change and agriculture in Brazil, with focus on policy developments (including action plans and programs) and institutional make-up. In Brazil, the 5th largest emitter of greenhouse gases in the world, agriculture (including land use change and forestry) is the largest contributor to green house gas (GHG) emissions. The emission reduction potential of the agricultural sector (including land use change and forestry) is significant and not yet sufficiently explored. Brazil currently counts with 30 Clean Development Mechanism (CDM) projects in the agricultural sector (targeting only methane emission reductions and biomass generation), while there are no registered CDM projects in the country under the 'afforestation and reforestation' category. Agriculture is highly vulnerable to climate variability, particularly in the Brazilian semi-arid Northeast where droughts have had a significant impact on crop yields and people's livelihood. The extension and improvement of both irrigation infrastructure and climate-sensitive insurance coverage for agricultural production, as well as addressing the problems of severe land degradation, can reduce some of the observed vulnerabilities in the country. Reducing poverty and inequality in rural areas, and particularly in those areas already vulnerable to climate risk, can also contribute to minimizing the negative impacts of future weather variability.